1995
DOI: 10.1111/j.1600-0536.1995.tb02072.x
|View full text |Cite
|
Sign up to set email alerts
|

The development and course of test reactions to gold sodium thiosulfate

Abstract: In our department, gold sodium thiosulfate has become the 2nd most common allergen in routinely patch tested dermatitis patients, with a rate around 10%. Test reactions to this compound often appear late, sometimes so late that active sensitization may be suspected. This study was performed to study the time course of the allergic reaction to gold sodium thiosulfate and to elucidate whether late test reactions mean active sensitization. 10 patients with contact allergy to gold sodium thiosulfate (0.5% pet.) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
2
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 22 publications
7
68
2
3
Order By: Relevance
“…Occasionally or frequently, most sensitizers seem to behave like this, with test reactions appearing later than on the ordinary reading day, D2 to D4. Gold and certain therapeutic agents such as corticosteroids and neomycin have this tendency (48)(49)(50). The significance of a late appearing, and hence possibly undetected, contact allergy differs according to the sensitizers involved.…”
Section: Negative Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally or frequently, most sensitizers seem to behave like this, with test reactions appearing later than on the ordinary reading day, D2 to D4. Gold and certain therapeutic agents such as corticosteroids and neomycin have this tendency (48)(49)(50). The significance of a late appearing, and hence possibly undetected, contact allergy differs according to the sensitizers involved.…”
Section: Negative Reactionsmentioning
confidence: 99%
“…On being repeated, the test is already positive at 2-4 days. However, it has recently been demonstrated that positive patch test reactions to gold salts can appear after 10 days without being due to patch test sensitization (50). Re-testing a patient after an interval may also reveal patch test sensitization, although there has been no known flareup reaction (52).…”
Section: Patch Test Sensitizationmentioning
confidence: 99%
“…When patch tests are followed over an extended period of time, late-appearing reactions and longlasting reactions are considered to indicate allergic reactions. Positive patch test reactions to gold appear late and they are extremely long-lasting (1,14,18,23,(37)(38)(39).…”
Section: Establishment Of Contact Allergymentioning
confidence: 99%
“…When patch testing patients with suspected adverse reactions to dental materials with higher concentrations of either gold thrichloride or gold sodium thiosulfate, a higher number of patients with a clinically relevant contact allergy to gold was found (26,(57)(58)(59)(60). Whenever patch testing with gold, keep in mind that a test reading should also be performed after 1 week (38,39). Actually, read-ing even on D 14-21 may be indicated (38,39).…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation